2010
DOI: 10.2522/ptj.20080298
|View full text |Cite
|
Sign up to set email alerts
|

Hallux Valgus and the First Metatarsal Arch Segment: A Theoretical Biomechanical Perspective

Abstract: Hallux valgus is a progressive foot deformity characterized by a lateral deviation of the hallux with corresponding medial deviation of the first metatarsal. Late-stage changes may render the hallux painful and without functional utility, leading to impaired gait. Various environmental, genetic, and anatomical predispositions have been suggested, but the exact cause of hallux valgus is unknown. Evidence indicates that conservative intervention for hallux valgus provides relief from symptoms but does not revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
106
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 81 publications
5
106
0
2
Order By: Relevance
“…This advice is also germane for research planning to quantify MPD in patient populations. Additionally, since collapse of the arch is a common predisposition of hallux valgus, 27,30,42 radiographic distortion attributed to arch height may, in part, explain why first metatarsal protrusion has been so consistently recorded on radiographs in the study of hallux valgus. Because this study measured MPD with 3-D methods instead of single-plane radiographs, and recorded the measure in relation to the navicular, which is novel, we cannot know whether these findings are indicative of the cohorts sampled, or a manifestation of the methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This advice is also germane for research planning to quantify MPD in patient populations. Additionally, since collapse of the arch is a common predisposition of hallux valgus, 27,30,42 radiographic distortion attributed to arch height may, in part, explain why first metatarsal protrusion has been so consistently recorded on radiographs in the study of hallux valgus. Because this study measured MPD with 3-D methods instead of single-plane radiographs, and recorded the measure in relation to the navicular, which is novel, we cannot know whether these findings are indicative of the cohorts sampled, or a manifestation of the methods.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30][31][32] Therefore, measurements of MPD cannot be compared to data acquired by conventional radiographic methods. This limitation is notable, because despite the advancements in 3-D image-based technology, 35,37,38 radiographic evaluations remain the standard in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have suggested that the pressure exerted on medial side of the foot and capsule of the irst metatarsophalangeal joint may cause development and progression of HV deformity [12,23]. Therefore, we aimed to determinate how much the amount of navicular drop would affect the HV angular severity and foot-speci ic health related quality of life in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Resulting from previous there are changes in position of the foot muscles [2,8]. The deformation is considered to be progressive and irreversible [4,10]. According to different sources HV occurs in about 23% of population [7] and is associated with female gender, older age, and pain in other bodily regions [9].…”
Section: Introductionmentioning
confidence: 99%